ShadeMotion: tree shade patterns in coffee and cocoa agroforestry systems - Eduardo Somarriba; Randall Zamora; José Barrantes; Fergus L. Sinclair; Francisco Quesada (Agroforestry Systems, 2023)

Climate change adaptation in and through agroforestry: four decades of research initiated by Peter Huxley - Meine van Noordwijk; Richard Coe; Fergus L. Sinclair; Eike Luedeling; Jules Bayala; Catherine W. Muthuri; Peter Cooper; Roeland Kindt; Lalisa Duguma; Christine Lamanna; Peter A. Minang (Mitigation and Adaptation Strategies for Global Change, 2021)
Agroforestry (AF)-based adaptation to global climate change can consist of (1) reversal of negative trends in diverse tree cover as generic portfolio risk management strategy; (2) targeted, strategic, shift in resource capture (e.g. light, water) to adjust to changing conditions (e.g. lower or more variable rainfall, higher temperatures); (3) vegetation-based influences on rainfall patterns; or (4) adaptive, tactical, management of tree-crop interactions based on weather forecasts for the (next) growing season. Forty years ago, a tree physiological research tradition in aboveground and belowground resource capture was established with questions and methods on climate-tree-soil-crop interactions in space and time that are still relevant for today’s challenges. After summarising early research contributions, we review recent literature to assess current levels of uncertainty in climate adaptation assessments in and through AF. Quantification of microclimate within and around tree canopies showed a gap between standard climate station data (designed to avoid tree influences) and the actual climate in which crop and tree meristems or livestock operates in real-world AF. Where global scenario modelling of ‘macroclimate’ change in mean annual rainfall and temperature extrapolates from climate station conditions in past decades, it ignores microclimate effects of trees. There still is a shortage of long-term phenology records to analyse tree biological responses across a wide range of species to climate variability, especially where flowering and pollination matter. Physiological understanding can complement farmer knowledge and help guide policy decisions that allow AF solutions to emerge and tree germplasm to be adjusted for the growing conditions expected over the lifetime of a tree.

In memoriam: Peter A. Huxley (1926–2019) - Björn Lundgren; P. K. Nair; Meine van Noordwijk; Chin K. Ong; Fergus L. Sinclair; Ric Coe; Peter Cooper; Ken Giller; Catherine Muthuri; Shibu Jose (Agroforestry Systems, 2020)

Understanding patterns of tree adoption on farms in semi-arid and sub-humid Ethiopia - Miyuki Iiyama; Abayneh Derero; Kaleb Kelemu; Catherine Muthuri; Ruth Kinuthia; Ermias Ayenkulu; Evelyn Kiptot; Kiros Hadgu; Jeremias Mowo; Fergus L. Sinclair (Agroforestry Systems, 2017)

Effects of light environment on maize in hillside agroforestry systems of Nepal - Thakur Prasad Tiwari; Robert M. Brook; Paul Wagstaff; Fergus L. Sinclair (Food Security, 2012)

Morphological and AFLP diversity in Thaumatococcus daniellii, the source of the protein sweetener thaumatin - Wojciech S. Waliszewski; Fergus L. Sinclair; Katherine A. Steele (Genetic Resources and Crop Evolution, 2012)

Exotic tree species displace indigenous ones on farms at intermediate altitudes around Mount Kenya - Katja Kehlenbeck; Roeland Kindt; Fergus L. Sinclair; Anthony J. Simons; Ramni Jamnadass (Agroforestry Systems, 2011)

The effect of land use systems on tree diversity: farmer preference and species composition of cocoa-based agroecosystems in Ghana - Luke C. N. Anglaaere; Joseph Cobbina; Fergus L. Sinclair; Morag A. McDonald (Agroforestry Systems, 2011)

The role of local knowledge in determining shade composition of multistrata coffee systems in Chiapas, Mexico - Lorena Soto-Pinto; Víctor Villalvazo-López; Guillermo Jiménez-Ferrer; Neptalí Ramírez-Marcial; Guillermo Montoya; Fergus L. Sinclair (Biodiversity and Conservation, 2007)

Population status and gender imbalance of the marula tree, Sclerocarya birrea subsp. caffra in northern Namibia - Elizabeth Nghitoolwa; John B. Hall; Fergus L. Sinclair (Agroforestry Systems, 2003)

A general classification of agroforestry practice - Fergus L. Sinclair (Agroforestry Systems, 1999)

Preface - Fergus L. Sinclair (Agroforestry Systems, 1995)